'Once upon a time ago': An Interdisciplinary Collaboration Between Archaeology, Museology and Pedagogy. (2nd October 2018) - Toftdal, Mia; Kirk, Sidsel; Pécseli, Benedicta
Abstract : A partnership between the Museum of Copenhagen and the University College Copenhagen has investigated the potential of incorporating archaeology into pedagogical student practices in kindergartens. Through an interdisciplinary collaboration between archaeology, museology and pedagogy, the project has provided new knowledge as to how encounters between young children and archaeology can contribute to the development of learning abilities and the general formation of the children. Archaeological finds have an instant fascination and a great strength in that they are physically available due to their materiality. The project "Once upon a time ago" has shown new ways of addressing the access to cultural heritage and history to young children aged 2 to 5, and it has exposed the great potential of not only learning about archaeology, but learning through archaeology. GRAPHICAL ABSTRACT: UF0001 Abstract :